Analisis Konsep Dasar Media Pembelajaran Pada Sekolah Dasar - Nisya Frasetia; Faarah Salsabila; Azizah Abi Jasmine; Rika Aprilia; Wismanto Wismanto (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Learning requires appropriate media support, which can be in the form of original objects around or production results, in order to support certain learning activities. In this process, the teacher acts as a facilitator who conveys messages to students, who then become intermediaries to gain knowledge. This research aims to determine the learning process that involves teachers as directors and students as learning intermediaries to receive information in cognitive, affective and psychomotor forms. The research used is literary study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. The results of the research show that learning media is needed to (1) increase learning effectiveness through student movement and thinking, (2) optimize the use of learning media for successful student learning, (3) adapt to curriculum developments for successful learning.